Rethinking Cultural-Historical Theory A Dialectical Perspective to Vygotsky - Dafermos, Manolis (Perspectives in Cultural-Historical Research,, 2018)
This book is an exploration of science in the making. It offers readers the opportunity to critically reflect on the process of development of Vygotsky's research program from the perspective of dialectics, focusing on the dramatic process of building and rebuilding cultural historical theory. Vygotsky's creative and dramatic journey is no less important than the concrete results of his research. An epistemological and historical investigation of the formulation of cultural historical theory sheds light on the process of knowledge production and reveals hidden dimensions of creativity in science.